Curriculum on Information Services for Education of Health Information Professionals - Rama Raj Urs, R. (Journal of Information and Knowledge, 2001)
Specialized training in required is the management of health science libraries and information centries. For the Post-graduate training programme designed by the Rajiv Gandhi University of Health Sciences in Kamataka for the health science information professionals a curriculum has been designed. The regulations framed for the P.G. Diploma Course are also described.